Analysis of the Need for Padlet-Based Learning Media Development to Improve Understanding of Concepts in Class XI Circular Motion Material at SMA Kota Bengkulu - Tri Yulistia (CV. Media Inti Teknologi, 2024)
An effective learning tool is one that can boost students' interest and motivation. Padlet is an easy-to-use, maintain, and set-up collaborative platform. This study set out to find out what educators and students needed in order to create lesson plans for high school students using the Padlet software. The methodology used in this study was qualitative descriptive. The data was gathered through observations, interviews, and literature research. This research instrument consists of these observation and interview sheets. The technique for data analysis is qualitative descriptive data analysis. The results of the learning materials, interviews, and observations that were done show that there is still space for development in the students' conceptual understanding, especially when it comes to the material on circular motion. because students still find it difficult to understand the material they are studying and professors still use a traditional teaching methodology. Therefore, it can be said that Padlet-based development media are still needed at SMAN 1 Kota Bengkulu, SMAN 3 Kota Bengkulu, and SMAN 9 Kota Bengkulu in order to support students' learning and help them understand concepts. This is based on the needs analysis that was conducted at these schools.